Global liquidity glut or global savings glut? A structural VAR approach - Thierry Bracke; Michael Fidora (European Central Bank (ECB), 2008)
Since the late-1990s, the global economy is characterised by historically low risk premia and an unprecedented widening of external imbalances. This paper explores to what extent these two global trends can be understood as a reaction to three structural shocks in different regions of the global economy: (i) monetary shocks (“excess liquidity” hypothesis), (ii) preference shocks (“savings glut” hypothesis), and (iii) investment shocks (“investment drought” hypothesis). In order to uniquely identify these shocks in an integrated framework, we estimate structural VARs for the two main regions with widening imbalances, the United States and emerging Asia, using sign restrictions that are compatible with standard New Keynesian and Real Business Cycle models. Our results show that monetary shocks potentially explain the largest part of the variation in imbalances and financial market prices. We find that savings shocks and investment shocks explain less of the variation. Hence, a “liquidity glut” may have been a more important driver of real and financial imbalances in the US and emerging Asia than a “savings glut”.
Keywords: E2; F32; F41; G15; 330; current account; global imbalances; global liquidity; investment drought; savings glut; structural VARs; Außenwirtschaftliches Gleichgewicht; Währungsreserven; Geldmenge; Sparen; Investition; Schock; VAR-Modell; EU-Staaten; Schwellenländer; Asien; USA